2019
DOI: 10.3389/fnins.2019.00633
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Gene Expression and Identification of Biological Regulatory Mechanisms in Alzheimer's Disease

Abstract: Alzheimer's disease (AD), also known as senile dementia, is a progressive neurodegenerative disease. The etiology and pathogenesis of AD have not yet been elucidated. We examined common differentially expressed genes (DEGs) from different AD tissue microarray datasets by meta-analysis and screened the AD-associated genes from the common DEGs using GCBI. Then we studied the gene expression network using the STRING database and identified the hub genes using Cytoscape. Furthermore, we analyzed the microRNAs (miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 71 publications
(74 reference statements)
0
31
0
Order By: Relevance
“…All these phenomena are linked to the aberrant cell cycle re-entry that aged neurons initiate [36]. Heterochromatin modifications, in turn, result in decreased rRNA synthesis and induce nucleolar stress, affecting ribosome number, protein transduction, and gene expression [37][38][39]. In the nervous system, Lamins A/C, B1, and B2 present different expression levels and are instrumental for embryonary development and postnatal survival [40].…”
Section: Introductionmentioning
confidence: 99%
“…All these phenomena are linked to the aberrant cell cycle re-entry that aged neurons initiate [36]. Heterochromatin modifications, in turn, result in decreased rRNA synthesis and induce nucleolar stress, affecting ribosome number, protein transduction, and gene expression [37][38][39]. In the nervous system, Lamins A/C, B1, and B2 present different expression levels and are instrumental for embryonary development and postnatal survival [40].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a combination of RJ and floral pollens resulted in significant amelioration of depressive symptoms, along with improvement of problem-solving capacity in postmenopausal women [ 126 , 127 ]. On top of this, the literature showed that RJ has the potential to improve general mental health of healthy volunteers [ 197 ]. It also documents antidepressant effects of RJ in animal models of depression and anxiety [ 201 , 212 ].…”
Section: Discussionmentioning
confidence: 99%
“…RJ is reported to improve testosterone, dehydroepiandrosterone sulfate, and estradiol in healthy adults [ 197 , 198 ]. It is widely used to treat infertility because of its phytoestrogen content [ 87 , 199 ].…”
Section: Mechanisms Underlying Effects Of Rj On Cognition and Ad-rmentioning
confidence: 99%
“…Strikingly, Serpin3a (the human analogue of Serpina3n) displays the highest fold-changes in the brains of schizophrenia patients (2-fold increase, P = 1.14E-13, FDR = 1.62E-10), and two-fold increase in autism ( P = 0.004154, FDR = 0.059) 48 . Serpina3 is also overexpressed in Alzheimer’s as it enhances amyloid beta fibrillization and accelerated plaque formation 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%